University patenting in Germany before and after 2002: What role did the professors' privilege play? - Sidonia von Ledebur; Guido Buenstorf; Martin Hummel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We examine ownership patterns of German university-invented patents before and after the abolition of the professors' privilege in 2002 to explore how the legal change affected patenting activities. Our data show a shift from individually-owned and firm-owned patents to university-owned patents, which becomes increasingly strong over the years. Differences in the patent experience of inventors and universities further help explain the variance in ownership patterns. Both experienced and inexperienced inventors are affected by the legal change.
Keywords: O33; O34; O38; 330; university patenting; technology transfer; professors' privilege; Germany; Hochschulforschung; Patent; Erfindung; Technologietransfer; Hochschulrecht; Reform; Wirkungsanalyse; Deutschland